2017
DOI: 10.1007/s10578-017-0750-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Police Injustice, Moral Disengagement, and Aggression Among Juvenile Offenders: Utilizing the General Strain Theory Model

Abstract: Although many juvenile offenders report experiencing police injustice, few studies have examined how this source of strain may impact youths' behavioral outcomes, including risk for future recidivism. This study begins to address that gap in the literature. We applied the general strain theory as our theoretical framework to examine the interactive effect of perceived police injustice and moral disengagement on juvenile aggressive behavior. Our sample included 95 juvenile offenders who completed questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
1
8
1
2
Order By: Relevance
“…They kept them in the police lock-ups for many days without judicial remand (approval). However, this study does not prove or suggest that the police's misconduct resulted in recidivism among juveniles-as Zapolski et al (2018) and Kane (2005) found in their studies.…”
Section: The Role Of Police As the Gatekeepers And Divertercontrasting
confidence: 83%
See 1 more Smart Citation
“…They kept them in the police lock-ups for many days without judicial remand (approval). However, this study does not prove or suggest that the police's misconduct resulted in recidivism among juveniles-as Zapolski et al (2018) and Kane (2005) found in their studies.…”
Section: The Role Of Police As the Gatekeepers And Divertercontrasting
confidence: 83%
“…The police are gatekeepers. They have an extremely critical role in preventing children from recidivism (Wilson et al, 2018;Zapolski et al, 2018). In the JJSA, in minor offences, the police could divert (by providing bail to) a child from the detention centre and could reduce recidivism rates among juveniles.…”
Section: The Role Of Police As the Gatekeepers And Divertermentioning
confidence: 99%
“…The theory asserts that various forms of strain (e.g., life stress and negative social relationships) can cause stressful feelings and negative emotions and subsequently lead to deviant behaviors or addiction as a coping strategy or escape from the negative feelings ( Agnew & White, 1992 ). The theory was originally developed to explain delinquency and crime ( Agnew, 1992 ), and has been widely applied in various problematic behaviors, such as Internet addiction ( Jun & Choi, 2015 ), substance use ( Özbay, 2014 ; Sharp, Peck, & Hartsfield, 2012 ), problematic alcohol consumption ( Swatt, Gibson, & Piquero, 2007 ), disordered eating ( Piquero, Fox, Piquero, Capowich, & Mazerolle, 2010 ), aggression ( Zapolski, Banks, Lau, & Aalsma, 2018 ), cyberbullying ( Jang, Song, & Kim, 2014 ), and commercial sexual exploitation ( Reid & Piquero, 2016 ). Strain is a critical factor that causes individuals to conduct problematic behaviors ( Agnew, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strain is a critical factor that causes individuals to conduct problematic behaviors ( Agnew, 1992 ). A variety of strains have been found to result in such behaviors including academic stress, negative emotions, negative experiences in childhood, intimate partner violence, maternal depression, lack of social support, and parental criminality ( Agnew, 1992 ; Jang et al., 2014 ; Jun & Choi, 2015 ; Reid & Piquero, 2016 ; Zapolski et al., 2018 ). In our case, masculine role discrepancy was found as a stressor; it would be associated with increased tension and negative feelings related to masculine role discrepancy; discrepancy stress in turn would increase the problematic behavior of addictive use of SNSs.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the relationship between negative affects and perceived police procedural and distributive justice. Nonetheless, the general findings of these studies indicate a positive link between perceived procedural injustice exhibited by police (police-related strain; e.g., police officers’ dishonesty, discourtesy, disrespectful behavior, and discrimination against minorities) and negative emotions or poor mental well-being (e.g., anger, frustration, resentment), which subsequently increase the likelihood of criminal offending [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%